Perancangan Pemasaran Digital Untuk Produk UMKM untuk Meningkatkan Promosi Produk di Kabupaten Agam - Al Muzacy, Zio Farid; Annas, Firdaus; Jamil, Hafizin; Ramadhani, Yessi (Yayasan Lembaga Studi Makwa, 2023)
The development of digital technology offers significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand their market reach and enhance product competitiveness. However, many MSMEs still face challenges in effectively utilizing technology for marketing purposes. This study aims to design a marketing system based on the OpenCart platform tailored to the needs of three MSMEs in Agam Regency: Ay-la Goat Milk, 3 Saudara Nursery, and Nirwana Flower Studio. The research method applied in this study is Research and Development (R&D) with the ADDIE model approach, encompassing five stages: needs analysis, design, development, implementation, and evaluation. The findings indicate that the developed system effectively supports MSMEs in managing product marketing more efficiently, featuring product management, transaction processing, and promotional tools. The implementation of this system not only enhances MSME operational efficiency but also broadens their market access in the digital realm. Therefore, this research contributes positively to accelerating the digital transformation of MSMEs in Agam Regency.